Stereocomplex-type polylactide with bimodal melting temperature distribution: Toward desirable melt-processability and thermomechanical performance. (15th April 2019) - Liu, Zhenwei; Fu, Meirui; Ling, Fangwei; Sui, Guopeng; Bai, Hongwei; Zhang, Qin; Fu, Qiang
Abstract: Recently, stereocomplex-type polylactide (SC-PLA) has generated growing interest because the unique SC crystals can provide drastic improvement in the heat/chemical resistances and durability of bio-derived and biodegradable PLA, exhibiting great potential to compete with some petroleum-derived engineering plastics in diverse applications. However, SC-PLA suffers from poor melt memory effect as well as significant thermal degradation after being completely melted at temperatures above 250 °C, which make it challenging to converse SC-PLA into useful products using versatile melt-processing technologies. With these challenges in mind, in this work, we propose a facile and practical strategy to fabricate SC-PLA products with exceptional thermomechanical properties through low-temperature melt-processing of SC-PLA powder with a bimodal melting temperature distribution. The results show that the melting temperature ( T m ) bimodality makes SC-PLA powder able to be easily injection molded at a relatively low temperature of 210 °C (between the two T m s) due to the selective melting of the low- T m SC-PLA component (SC- l PLA, ca. 20–40 wt%), indicating a good melt-processability. Meanwhile, the high- T m SC-PLA (SC- h PLA) component can directly deliver its desirable properties to the injection molded SC-PLA products. More importantly, during the injection molding process, the unmelted SC- h PLA particles can also induce the exclusive SC crystallization of the SC- l PLA melt as nucleating agent and greatly amplify the shear stress imposed on the melt as "rigid particles", finally generating numerous oriented SC structure in the SC- l PLA. Consequently, the injection molded SC- h PLA/SC- l PLA products exhibit impressively high tensile strength (74.3 MPa) and Vicat softening temperature (211.6 °C). Overall, this work presents an effective guidance for achieving desirable melt-processability of SC-PLA without sacrificing its thermomechanical properties and provides an industrial processing route towards high-performance SC-PLA products. Graphical abstract: Image 106841 Highlights: SC-PLA products were fabricated by low-temperature melt-processing of bimodal SC-PLA powder. The melting temperature bimodality plays a key role in achieving balanced melt-processability and product performance. The SC- l PLA component can provide the powder with good low-temperature melt-processability. The SC- h PLA component can endow the melt-processed products with exceptional thermomechanical performance. SC- h PLA induced exclusive SC formation and crystal orientation can also contribute to the enhanced performance.